Hybridisation among hospital managers: the association between the use of control systems and healthcare management - Damián Encalada-Avila; David Naranjo-Gil (Journal of Health Organization and Management, 2026)
Purpose Drawing on New Public Management this study examines whether senior hospital managers' professional training profiles are associated with their use of management control systems in public hospitals. It examines whether medically trained, managerially trained and hybrid clinical–managerial executives differ in their use of Simons's four levers of control – belief, interactive, diagnostic, and boundary systems – and how these levers relate to care-related and managerial objectives. Design/methodology/approach A cross-sectional survey of 58 senior managers in Ecuadorian public hospitals covered 50.4% of the hospitals registered with the Ministry of Public Health at the time of data collection. The hypotheses were tested using partial least squares structural equation modelling (PLS-SEM). The analysis assessed measurement reliability and validity, effect sizes and out-of-sample predictive performance. Given the moderate sample size and single-source design, the findings are interpreted as exploratory. Findings Medical training was associated with greater use of belief and interactive systems and with less use of diagnostic and boundary systems. Hybrid clinical–managerial training was associated with the use of all four levers. Belief and interactive systems were positively associated with care-related objectives, whereas diagnostic and boundary systems were positively associated with managerial objectives. Originality/value The study links professionalism, management control systems, and public-sector healthcare in an under-researched Latin American setting. It shows how hybrid training may support a broader repertoire of control practices in centralised, resource-constrained public hospitals.